The usefulness of an application-supported nutritional intervention on non-high-density lipoprotein cholesterol in people with a risk of lifestyle-related diseases. - Yuko Noda; Mitsuhiro Kometani; Akihiro Nomura; Masao Noda; Rie Oka; Mayuko Kadono; Takashi Yoneda (PLOS Digital Health)
Lifestyle-related diseases, such as diabetes, are mostly caused by poor lifestyle habits; therefore, modifying these habits is important. In Japan, a system of specific health checkups (SHC) and specific health guidance (SHG) was introduced in 2008. The challenges faced include low retention rates and difficulty in maintaining results. Digital technologies can support self-management and increase patient convenience, although evidence of the usefulness of this technology for SHG is limited. This study evaluated the usefulness of nutritional guidance using a smartphone application (app) added to conventional SHG. We recruited eligible participants for SHG in Japan from November 2018 to March 2020. We assigned them to "Intervention Group: Application-Supported Nutrition Therapy" or "Control Group: Human Nutrition Therapy" based on their desire to use the app. The primary outcome was a change in non-high-density lipoprotein cholesterol (non-HDL-C) levels post-intervention. The secondary outcomes were a change in lipid profile, metabolic indices, and frequency of logins to the app. We assessed 109 participants in two cohorts: 3-month (short-term) and 6-month (long-term). The short-term cohort had 23 intervention and 29 control participants, while the long-term cohort had 35 and 22, respectively. There was a significant improvement in non-HDL-C levels in the short-term intervention group compared to the control group. There was no significant difference in non-HDL-C levels in the long-term groups or at 1 year. There were significant improvements in body weight (BW) in the short-term cohort until 1 year compared within the groups. The retention rate remained high in the short-term cohort (92%) but decreased to 57.8% at 6 months in the long-term cohort. Using an app system to facilitate dietary recordings and guidance for patients at risk of lifestyle-related diseases led to improved lipid levels and BW. These benefits persisted to some extent after 1 year. This app may partially supplement conventional SHG.